THE IMPLEMENTATION OF MULTICULTURAL VALUES IN THE EDUCATIONAL INSTITUTION - Slamet, Slamet; Masrukhi, Masrukhi; Haryono, Haryono; Wasino, Wasino (Universitas Negeri Semarang, 2017)
Education that is charged with multicultural values ​​is a staged-educational process that can be used as a binder and a bridge to accommodate differences, such as ethnicity, language, culture, gender, region, and religion in a multi-cultural society in order to create intelligent, wise, and polite personality in dealing with diversity issues. Multicultural education should continue to be understood comprehensively, so it is not stagnant only limited to discourse, and ultimately can be implemented in harmony and without any negative effects. It is this basis that causes multicultural education urgent for immediate implementation in educational institutions, so it is necessary to comprehensively study various aspects of life so that there is a synergy between the academic community and the society of a nation-state. This study employed a research and development (R & D) design from Borg and Gall, while the design of the model was adopted from the development of McKenny. The research procedure was based on the ten-phased design from Borg and Gall that has been modified into three phases, namely (1) a preliminary study; (2) the development of the design; and (3) testing the feasibility of the product. Based on the conclusion, this study recommends that multicultural education is a new discourse of education in Indonesia, but the urgency of its implementation is very high; the multicultural education curriculum can be implemented through each level of education, the student program and in the process of habituation through daily learning both within the school and in the family. Multicultural education can be inserted through the planting of multicultural values ​​into the curriculum or learning activities which are responsively multicultural by promoting respect for differences: racial, ethnic, cultural, religious, and territorial between the community members; and no less important is that multicultural education discourse can be implemented within the scope of the family, as the smallest social institution in the community which is most effective learning media in the process of internalization and transformation of values, as well as the socialization of family members.